Social Insects—I. Ants - KACHROO, P. (SCHOOL SCIENCE, 2006)
Insects are grouped under the Class Insecta of the’ animal kingdom. More than a million different species of insects have been described and named so far. Individuals belonging to many of these species are numerous and are sometimes described as ‘clouds darkening the sky’ and ‘swarms carpeting the ground for miles’. Some insects are large enough to be visible but a large majority are minute and can hardly be seen without the help of a magnifying glass. Notwithstanding their small size, the total bulk of animal matter in their bodies added together would exceed that of all the other land animals.